اﺑن ﻓﺿﻼن وﻣﻧظوره ﻟﻘﯾﻣﺔ اﻟﺟزﯾﺔ (م١٢٣٤ــــ ١١٧٢) / (ھـ٦٣١ــــ٥٦٨ ) (Journal of the College of Education for Women, 2019)
Varied conditions of dhimmi in Baghdad during the Abbasid era, which created a situation of conflicting views, misunderstanding and differences in the analysis of most historians and orientalists in the center of that the research tries to look up to explore the kind of relationship between the Abbasid Caliphate as the highest religious authority and secular in the Arab Islamic state and dhimmi through the character of Ibn Fadlan world Muslim jurist familiar with the mysteries of many of the reality of life in Baghdad by his accession to the post injury and headed to the top of the pyramid of the judiciary stint as elimination of judges (Chief Judge) and his term of office (Jawala) twice and presented un economic study reqested for it raising the value of the tribute imposed on the dhimmi based on "to the height of the living situation of dhimmi with support legitimate for that .The Caliph Nasser al-Din Allah sought to increase the resources of the State Finance. but those proposals rejected by the succession in that was the evidence of good treatment of the Arab Islamic nationals from the dhimmi with the research found a set of results relevant subsidiary.